Alloying of titanium by oxygen during chamber electroslag remelting - Ryabtsev, Anatoliy D.; Troyanskyy, Oleksandr A.; Pashynskyi, Volodymyr V.; Snizhko, Olga A. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The paper presents the results of alloying titanium by oxygen in the process of chamber electroslag remelting. As an oxygen-containing ligature, we used the electrodes-satellite from the reaction mass residues mixture from the retort lid for magnesium thermal reduction of a titanium sponge, a specially prepared gaseous argon oxygen mixture containing 30% oxygen applied directly to the melting space, micro-size (10-15 mm) powder particles of titanium oxide and titanium oxide nanopowder with a particle size of 21 ± 5 nm. The structure and the properties of titanium alloyed by oxygen from the oxygen-containing ligature, gas phase and titanium oxide powder during chamber electroslag remelting of the titanium sponge are investigated. It was found that at the oxygen content of 0.053%mas. to 0.22%mas. in the metal formed a homogeneous single-phase structure typical for commercial titanium formed by polyhedral grains of the α-phase. The increase of the oxygen concentration in titanium for more than 0.22%mas. leads to the formation of the microstructurewith a typical needle structure, which allows it to be classified as the α׳-phase.